High Intensity Interval Training Leads to Similar Inflammatory Activation as Seen With Traditional Training in Chronic Heart Failure - Taylor, Arlana G.; Ignaszewski, Andrew I.; Bredin, Shannon S. D.; Hill, John S.; Shellington, Erin M.; Warburton, Darren E. R. (Frontiers in Cardiovascular Medicine, 2022)
Background Inflammatory activation has been associated with the severity and progression of chronic heart failure (CHF). Although cardiac rehabilitation is an important therapy, acute bouts of exercise may lead to increases in pro-inflammatory cytokines with exercise intensity mediating these changes. Objective To evaluate the acute inflammatory response in patients living with CHF during a randomized trial following Steady State (SS) or High Intensity Interval (HIIT) training. Methods Patients living with CHF (n = 14) were stratified (for body mass and aerobic power) and randomized into SS and HIIT cycle exercise. The HIIT exercise training involved 2 min work:recovery phases at 90:40% heart rate reserve. The SS exercise training involved continuous exercise at 65% of heart rate reserve (matched total work). Acute inflammatory markers were evaluated (via ELISA) at baseline, immediately following the bout, and at 6, 24, and 48 h post-exercise. Results There was limited differences in the changes in inflammatory biomarkers across time between the HIIT and SS groups. Both groups experienced a significant (p < 0.05) change in Interleukin-6 immediately post-exercise. Conclusions A single bout of HIIT or SS does not result in excessive inflammatory activation in CHF patients. Acute HIIT and SS result in similar changes in inflammatory markers. These findings have important implications for exercise training and rehabilitation programs in persons living with CHF.